RESPONSIBILITY OF THE CONVEYANCER AGAINST SELLING LAND DEED - I Gusti Bagus Yoga Prawira (Jurnal IUS Kajian Hukum dan Keadilan, 2016)
Deed official Land Builders (PPAT) as the competent public authority to make the deeds of the land must have a special ability in the field of land so that the deed had made not to cause problems in the future given the deed he made could be used as evidence has the legal deed transfer of rights or cancellation of land rights. If the causes of the problems arise because of omissions by PPAT, then the deed resulted only have the force of law under the hand that can be cancelled due to nonfulfilment of the terms subjective. If the causes of the problems arise because of the dishonesty related client truth administrative requirements as the basis for certificates that can prove the certificates null and void due to nonfulfilment of objective requirements. Conclusion the results of the study are: 1. PPAT is a public official whose job is to make the deeds of certain particularly deed of transfer of rights over land as stipulated in Government Regulation No. 37, 1998, 2. PPAT was responsible for the deed he made either administrative, civil and criminal.Keyword : Land Deed Official ,The Deed Of Sale And Purchase Of Land